Recurrent Anti-AMPA Receptor Limbic Encephalitis: A Case Report and Literature Review - Fang, Yuanyuan; Pan, Dengji; Huang, Hao (Frontiers in Neurology, 2021)
Alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor encephalitis is a relatively rare anti-neuronal surface antigen autoimmune encephalitis (LE). We described a 47-year-old Chinese man case of anti-AMPA receptor limbic encephalitis initially presented with cognitive decline, undetectable antibodies, and normal imaging findings in magnetic resonance image (MRI) and then developed into typical autoimmune limbic encephalitis a few months later with a course of multiple relapses. In addition, we found progressive brain atrophy in our case, which was a rare presentation of LE. This report also summarized the characteristics of nine reported cases of anti-AMPA receptor limbic encephalitis with relapse up to date. This case highlights that autoimmune limbic encephalitis is an important differential diagnosis for patients with typical symptoms even when the MRI and antibodies are normal and more attention should be paid to the relapse of anti-AMPA receptor encephalitis.